Printing and embroidery ordering system - Omar Hairy Mohamad Alias (2023)
Technology is very important for each of us in facing the new global era. The evolution of technology will bring us to the new lifestyle and simultaneously it will possess our daily life activities. By having this technology, they many achieve their business target effectively and the business process will become efficiently.